AUDIT INTERNAL SEBAGAI VARIABLE MODERATING DAMPAK PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN STABILITAS KEUANGAN TERHADAP FINANCIAL STATEMENT FRAUD - Prestiani Putri, Adistie (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study analyzes the influence of Corporate Social Responsibility (CSR) and Financial Stability on Financial Statement Fraud in construction service sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. In addition, this study also evaluates the role of Internal Audit in moderating the relationship between Corporate Social Responsibility (CSR) and Financial Stability on Financial Statement Fraud in the same company. The method used in this study is a quantitative approach, with data analysis carried out using SPSS, and involving 95 data samples. The results of the study indicate that: (1) Corporate Social Responsibility (CSR) has a significant negative influence on Financial Statement Fraud in construction service sector companies listed on the IDX during 2019-2023; (2) Financial Stability has a significant positive influence on Financial Statement Fraud in construction service sector companies listed on the IDX during 2019-2023; (3) Internal Audit cannot moderate the influence of Corporate Social Responsibility (CSR) on Financial Statement Fraud in construction service sector companies listed on the IDX during 2019-2023; and (4) Internal Audit also cannot moderate the influence of Financial Stability on Financial Statement Fraud in construction service sector companies listed on the IDX during 2019-2023.